Milton and the English Auden. (September 2015) - Daniel, Clay
Unlike many modernists, W. H. Auden consistently esteemed Milton's poetry. Moreover, he often was stimulated by Milton's antipathetic cultural legacy, which, in the 1930s, he identified with the rise of the National Socialists. This identification, most clearly made in New Year Letter (1940) and Letter to Lord Byron (1936), also informs one of Auden's most well-known poems, "Lay Your Sleeping Head, My Love" (sometimes called "Lullaby") (January 1937). That poem carefully rewrites Milton's notions of love and religion, especially as they appear in "On Time, " to accord with Auden's sense of his own time.